A expansão da eucaliptocultura no estado de Minas Gerais e a configuração de novos usos do território - Teixeira, Georgia (2018)
In Minas Gerais, the eucalyptus plantations were developed by the charcoal steel industry and the cellulose and paper sector in the year 1940, in order to maintain the continuous supply of wood. Endowed with deposits of iron ore, profuse forests and rivers, Minas Gerais stands by the dynamism of its steel industry which was strengthened from the decade of 1960, with the institution of the Forest Code of 1965 and with the Program of Fiscal Incentives for Afforestation and Reforestation. At this time, the planting of eucalyptus intensified throughout the state, as a result of the development public policies, the advancement of forestry research, the evolution of silvicultural techniques and the partnership between universities and companies. In the decade of 1970, an ecological-economic zoning was established, devoting five priority areas to forestry called Forest Districts in which highlighted Jequitinhonha Valley, due to its tabular relief, providing the mechanization and the low price of land aroused the interest of large forest enterprises for the region. The objective of this work was to analyze the territorial implications of eucalyptus plantations in Minas Gerais, based on the approach of the socioenvironmental geography and the concept of territory used, a synonym for geographic space. From bibliographical surveys, field work and physical diagnosis in the area, it was verified the configuration new territory uses, especially in Jequitinhonha Valley Forestry District, which resulted in changes in the environmental systems and in the production and work relation.